Uwagi o Małym Dodatkowym Ruchu w Przestrzennym Układzie Współrzędnych - Zahorski, S. (Engineering Transactions, 1965)
Several kinematic and physical relations are discussed for a small motion superposed over a fundamental motion in a fixed spatial reference frame.The present paper constitutes a complement to the previous work of the same author [1], in which similar problems are treated in a convected set of coordinates.